A Whiteheadian Business Ethics and the Western Hemisphere - Ulshöfer, Gotlind B. (Journal of business ethics, 2000)
The first part of my presentation is a short outline of how a feminist, process-oriented, i.e. in a Whiteheadian tradition, business ethics may look like. In the second part, I want to apply this approach in the field of American foreign trade policy concerning the extension of the North American Free Trade Area (NAFTA) to a free trade zone of the Western Hemisphere. I want to focus on ethical problems for the business of the Free Trade Area of the Americas. By taking my business ethics approach into consideration, I want to open up perspectives for a Whiteheadian view of the problem of the Free Trade Area.